2021
DOI: 10.3892/ijo.2021.5187
|View full text |Cite
|
Sign up to set email alerts
|

Clinical crosstalk between microRNAs and gastric cancer (Review)

Abstract: Globally, there were over 1 million new gastric cancer (GC) patients in 2018 and GC has become the sixth most common cancer worldwide. GC caused 783,000 deaths worldwide in 2018, making it the third most deadly cancer type. miRNAs are short (~22 nucleotides in length) non-coding RNA molecules, which can regulate gene expression passively at a post-transcriptional level. There are more and more in-depth studies on miRNAs. There are numerous conclusive evidences that there is an inseparable link between miRNAs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 136 publications
0
16
0
Order By: Relevance
“…Accumulating evidence suggests that various non-coding regulatory miRNAs, including miR-27a, miR-196a-1, miR-208a and miR-206, also serve a prominent role in the activation of the Wnt/β-catenin signaling pathway by inactivating SFRP1, which induces GC cell proliferation, migration, invasion and metastasis (46,(75)(76)(77)(78)(79)(80). In addition, long non-coding RNAs (lncRNAs) are also emerging as key players in mediating this process (81).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that various non-coding regulatory miRNAs, including miR-27a, miR-196a-1, miR-208a and miR-206, also serve a prominent role in the activation of the Wnt/β-catenin signaling pathway by inactivating SFRP1, which induces GC cell proliferation, migration, invasion and metastasis (46,(75)(76)(77)(78)(79)(80). In addition, long non-coding RNAs (lncRNAs) are also emerging as key players in mediating this process (81).…”
Section: Discussionmentioning
confidence: 99%
“…MALAT1, a competing endogenous RNA of miR-23b-3p, was shown to reduce the suppressive activities of miR-23b-3p on ATG-12, while simultaneously increasing the development of ATG-12, resulting in chemoinduced GC cell autophagy and drug resistance (YiRen et al, 2017). In addition, AKT and mTOR have been reported to be targeted via miR-495 overexpression of miR-495, which could prevent the growth in addition to induce the apoptosis of GC cells through blocking of PI3K/AKT/mTOR, which altered Bax, caspase-3/-9, and cyclin D1 expression (Ouyang et al, 2021). miR-153-3p facilitates ATG-7-mediated autophagy induction in fluorouracil resistance via the adenosine monophosphate (AMP)-activated protein kinase (AMPK)/ATG3 pathway in GC (Hou et al, 2020).…”
Section: Role Of Mirnas Through Regulation Of Autophagy In Gcmentioning
confidence: 99%
“…There are abundant convincing studies that showed inseparable association between miRNAs and GC (Shao et al, 2020). miRNAs affected GC, which includes oncogenesis, diagnosis, development, treatment, and prognosis, although many miRNAs have been linked to GC, and few could be useful to clinical practice (Ouyang et al, 2021), even though numerous miRNAs have been related to GC and few can be applied to clinical practice as well. Furthermore, dietrelated natural ingredients may control autophagy in the GC cell that promote cancer cell chemosensitivity (Xu et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that RAP2A can 3 Disease Markers regulate cell migration, cytoskeletal recombination, and other cellular processes [5][6][7]. In addition, it has been reported that RAP2A is upregulated in prostate cancer, thyroid cancer, nasopharyngeal cancer, and other human cancers [8][9][10]. However, the expression of RAP2A in GC has not been reported, except for one study that detected high expression of Rap2A in human hepatoblastoma HepG2 cells.…”
Section: Introductionmentioning
confidence: 99%